Aggravating factors and post COVID-19 conditions in COVID-19 patients complicated with autoimmune rheumatic diseases - Yoshihiko Ikeno; Fumiya Fukushima; Azusa Kikuchi; Ryouta Koike; Masafumi Arima; Kazuhiro Kurasawa; Kei Ikeda (Journal of Global Antimicrobial Resistance)
OBJECTIVES: Autoimmune rheumatic diseases (AIRD) are concerned to be underlying affecting the severity of COVID-19 and post COVID-19 conditions. In this study, we assessed aggravation factors and post COVID-19 conditions in patients with AIRD who developed COVID-19 and were treated in our hospital. METHODS: From January 2020 to Augst 2023, we conducted a retrospective survey of 1567 patients with rheumatic diseases (RA: n=788, others: n=779) treated in our hospital. In addition, among them, 66 patients developed COVID-19, confirmed by SARS-Cov2-ART (RA patients: n=43, other patients: n=23). We divided these patients into two groups, moderate to severe group (n=24) and mild group (n=42), and compared exacerbating factors based on clinical features and laboratory parameters between the two groups. In addition, we also assessed the appearance of post-COVID-19 conditions such as symptoms, lasting for more than 3 months after the onset, and compared between the two groups. RESULTS: The moderate to severe group was significantly older than the mild group (73.7±15.2 vs 61.4±13.6 yrs, p=0.0014), received higher dose of corticosteroid (5.37±2.57 vs 2.95±1.45 mg/day, p=0.0398), and showed higher rate of complicating with interstitial pneumonia (33.3 vs 13.0 %, p=0.0216). Post COVID-19 conditions were observed in 15 patients (22.7%). Its incidence was significantly higher in the moderate to severe group (n=10; 41.7%), compared with the mild group (n=5; 11.9%) (p=0.0017). CONCLUSION: In COVID-19 patients complicated with autoimmune rheumatic diseases, older age, corticosteroid dosage, and interstitial pneumonia were thought to be aggravating factors. Post COVID-19 conditions were frequently observed in moderate to severe patients.